A surface sensitive hard X-ray spectroscopic method applied to observe the surface layer reduction reaction of Co oxide to Co metal. Issue 43 (3rd November 2020) - Abe, Hitoshi; Niwa, Yasuhiro; Kimura, Masao
Abstract : In situ TREXS captures surface reactions. Abstract : A simple and easy surface sensitive spectroscopic method using hard X-rays has been developed and applied to observe the surface oxide reduction reaction. The method named TREXS, Total REflection X-ray Spectroscopy, records the total reflection of incident X-rays at sample surfaces. The surface reduction reaction of Co oxide (Co3 O4 ) to Co metal was successfully observed by in situ TREXS measurements with a surface sensitivity of ∼2 nm. The in situ TREXS measurements were performed under H2 flow of N2 balanced atmospheric pressure with increasing temperature. This method, in situ TREXS, will be a suitable and powerful tool to observe a variety of surface chemical reactions and consequently to understand catalytic processes under realistic operating conditions.